Nano-antioxidants: An emerging strategy for intervention against neurodegenerative conditions. (October 2015) - Sandhir, Rajat; Yadav, Aarti; Sunkaria, Aditya; Singhal, Nitin
Abstract: Oxidative stress has for long been linked to the neuronal cell death in many neurodegenerative conditions. Conventional antioxidant therapies have been less effective in preventing neuronal damage caused by oxidative stress due to their inability to cross the blood brain barrier. Nanoparticle antioxidants constitute a new wave of antioxidant therapies for prevention and treatment of diseases involving oxidative stress. It is believed that nanoparticle antioxidants have strong and persistent interactions with biomolecules and would be more effective against free radical induced damage. Nanoantioxidants include inorganic nanoparticles possessing intrinsic antioxidant properties, nanoparticles functionalized with antioxidants or antioxidant enzymes to function as an antioxidant delivery system. Nanoparticles containing antioxidants have shown promise as high-performance therapeutic nanomedicine in attenuating oxidative stress with potential applications in treating and preventing neurodegenerative conditions. However, to realize the full potential of nanoantioxidants, negative aspects associated with the use of nanoparticles need to be overcome to validate their long term applications. Highlights: The central nervous system is particularly vulnerable to oxidative stress. Conventional antioxidants are unable to cross blood brain barrier. Nanoencapsulation has emerged as an effective strategy to deliver antioxidants to brain. Advancements in nanocarrier system leads to targeted delivery.